Antioxidant Activity Test On Ethanol Extract Of Cassava Leaves (Manihot Esculenta C.) Using DPPH Method - Husain, Muhammad Hafizh; Febrianti, Dewi Retno; Salsabillah, Salma; Rolita, Ninda Norma; Amrullah, Kammal Nizam; Bawani, Elen Ayu; Ramadhani, Lailatul; Pratiwi, Lidia Wahyu; Yaqin, Ngainul; Jayanti, Angelina; Rafsanjani, Ramizard; Januarista, Terra; Faisal, Faisal; Ramadhan, Majida (Biopedagogia, 2024)
Cassava leaves (Manihot esculenta Crantz) are herbs used in traditional medicine. Cassava leaves contain secondary metabolite chemicals such as vitamin C, flavonoids, tannins, saponins, and triterpenes. Cassava leaves are pharmacologically active as anti-inflammatory, antibacterial, and antioxidants. To identify the sample's active antioxidant components using the DPPH technique. The DPPH method is a method of determining the antioxidant activity of a sample by examining its capacity to neutralize free radicals of the 2,2-diphenyl-1-picrylhydrazyl molecule. The antioxidant activity of quercetin from cassava leaf extract (Manihot esculenta Crantz) yielded an IC50 value of 210.33. The IC50 value shows that cassava leaves (Manihot esculenta Crantz) have modest antioxidant lower. Cassava leaves (Manihot esculenta Crantz) have antioxidant activity of 210.33 g/mL so they are included in the weak category in this study.